Quantum dot labelled antimalarials and investigation of their interaction with synthetic haemozoin - Ganazzoli, Giacomo (Department of Chemistry, 2019)
Chloroquine (CQ) is a well-known antimalarial drug acting through the inhibition of the formation of haemozoin crystals in the Plasmodium parasite’s digestive vacuole within human infected red blood cells. The formation of haemozoin is considered a defence strategy of the parasite in order to decrease the levels of toxic ferriprotoporphyrin (Fe(III)PPIX) present in the DV. Chloroquine is supposed to be adsorbed onto the fastest growing face of the crystal, inhibiting the growth and increasing the amount of toxic Fe(III)PPIX; however, the mechanism of this interaction is still largely unproven. The study of the interactions of CQ with both Fe(III)PPIX and β-haematin, haemozoin’s synthetic crystalline equivalent, can be used to clarify the mechanism of antimalarial action of CQ. In this project a CQ derivative was synthesized and labelled with quantum dots (QDs) in order to exploit their particular fluorescence properties during the investigation of the interaction. The synthesis of a chloroquine derivative was used in order to insert a primary amino function in the drug suitable for the coupling with QDs. The formation of this derivative (N 1 -(2-aminoethyl)-N 4 - (7-chloroquinolin-4-yl)-N 1 -methylpentane-1,4-diamine) was achieved through a four step reaction. After the extraction of chloroquine as a free base from diphosphate salt, it was desethylated. The insertion of the new group was obtained through a N-alkylation using a Boc protected aldehyde, leading to the formation of the final product by cleaving the Boc group with TFA. CdSe/ZnS quantum dots with carboxylic acid functionalized ligands (QD-COOHs) were obtained from Cytodiagnostics. Thanks to their dimension, they presented a fluorescence emission peak at 630 nm. During the characterization, the optimal fluorimeter conditions were found: excitation wavelength was set at 400 nm; photo multiplier voltage (PMT) of 1000 V; slow scan speed and slit widths of 10 nm for excitation and 5 nm for emission. Quantum dots were visualized using TEM technique and their dimension was confirmed. Thanks to previous studies carried out in this lab, a 0.01 M HEPES (pH 7.5) buffer was used for all the experiments in order to afford a good solubility of Fe(III)PPIX and a minimal QD-COOH emission quenching. In order to use QD-COOHs to study the interactions of CQ with Fe(III)PPIX and β-haematin it was necessary to attach the CQ derivative to QD-COOH. The carboxylate ligand coating allows the formation of covalent bonds, coupling the primary amine-function of chloroquine derivative (CQ- NH2) and QD-COOH. The reaction was completed using a two-step, one-pot process with 1-ethyl-3- (3-dimethylaminopropyl)carbodiimide (EDC) as a coupling agent. The product of the reaction, chloroquine derivative-labelled CdSe/ZnS quantum dot (QD-CQ), was characterized, recording the fluorescence emission spectrum with maximum intensity peak at 630 nm. In order to verify the achieved functionalization, SEM with EDS was used to detect the presence of Cl on the nanoparticles surface. TEM was also used to visualise the physical appearance of the QD-CQ. Labelled nanoparticles showed an enhanced tendency to aggregate than QD-COOH. The aggregation caused a decreasing of the fluorescence emission spectrum intensity. Sonication was shown to partially reduce QD-CQ aggregation and other experiments were done by adding a little quantity of different solvents (ethanol, methanol, acetone and 0.01 M HEPES pH 4.2) without significant improvements in enhancing fluorescence intensity. Fluorescence emission spectra of the interactions of the QD-COOHs with CQ and Fe(III)PPIX were then evaluated for comparison with those of the QD-CQ with both compounds. The final interaction studied was between β-haematin and the QDs. β-haematin was synthesised in 9.7 M acetate. TEM was used to visualise the interaction between QD-COOHs and QD-CQs with βhaematin. The QD-COOHs showed no selectivity in binding to the β-haematin crystals, whereas the QD-CQs bound primarily to the (001) face. This evidence supports theory that CQ adsorbs to the fastest growing face of β-haematin.